Green synthetic natural carbon dots derived from Fuligo Plantae with inhibitory effect against alcoholic gastric ulcer - Zhao, Yusheng; Cheng, Guoliang; Gao, Yushan; Cui, Luming; Zhao, Yafang; Zhang, Yifan; Tian, Yu; Zhao, Yan; Zhang, Yue; Qu, Huihua; Kong, Hui (Frontiers in Molecular Biosciences, 2023)
Fuligo Plantae (FP), the ash that sticks to the bottom of pots or chimneys after weeds burn, has long been used for its hemostatic and stomach-warming effects. Nevertheless, the active ingredient of FP still needs to be further explored. In this study, the microstructure, optical and chemical properties of FP-CDs were characterized by transmission electron microscopy, fourier transform infrared spectroscopy, fluorescence spectroscopy and X-ray photoelectron spectroscopy. An alcohol-induced gastric ulcer model was utilized to evaluate whether preadministration of FP-CDs alleviated gastric bleeding symptoms and ameliorated gastric mucosal barrier disruption. In addition, the feces of each group of rats were extracted for 16S rDNA genome sequencing of intestinal flora. The results confirmed that FP-CDs with a diameter ranging from 1.4-3.2 nm had abundant chemical groups, which may be beneficial to the exertion of inherent activity. FP-CDs alleviated alcohol-induced gastric ulcer, as demonstrated by activating the extrinsic coagulation pathway, alleviating inflammation, and suppressing oxidative stress levels. More interestingly, FP-CDs can improve the diversity and dysbiosis of intestinal flora in rats with alcohol-induced gastric ulcer. These comes about illustrate the momentous inhibitory effects of FP-CDs on alcoholic gastric ulcer in rats, which give a modern methodology for investigating the effective ingredient of FP, and lay an experimental basis for the application of FP-CDs in the clinical treatment of alcoholic gastric ulcer.